Foreign portfolio investment and economic growth - Duasa, Jarita; Kassim, Salina (Pakistan Institute of DEvelopment Economics, 2009)
This study examines the relationship between foreign portfolio investment (FPI) and Malaysia’s economic performance. In particular, the study analyzes the relationship between FPI and real gross domestic product (GDP) using the widely adopted Granger causality test and the more recent Toda and Yamamoto’s (1995) non-causality test to establish the direction of causation between the two variables. Similar method is also applied on the relationship between volatility of FPI and real GDP. Additionally, we adopt an innovation accounting by simulating variance decompositionsand impulse response functions for further inferences. Using the Malaysian quarterly data covering the period from 1991 to 2006, we find evidence that economic growth causes the FPI and its volatility. However, neither the FPI nor its volatility causes economic growth. The findings suggest that economic performance is the major pull factor in attracting FPI into the country. Thus, it is pertinent to ensure that the Malaysian economy remains on a healthy and sustainable growth path in efforts to maintain investor confidence in the economy.